Effect of repeated firings and staining on the mechanical behavior and composition of lithium disilicate - Miranda, Jean Soares [UNESP]; Barcellos, Aline Serrado de Pinho [UNESP]; Campos, Tiago Moreira Bastos; Cesar, Paulo Francisco; Amaral, Marina; Kimpara, Estevão Tomomitsu [UNESP] (Elsevier, 2020)
Objective: To evaluate the composition, flexural strength and fatigue behaviour of lithium disilicate ceramic (LD) after repeated firings and different staining techniques. Methods: LD discs were fabricated and divided according to number of firing cycles and staining technique: CO - control, discs were crystallized (850 °C/10 min); SC – single-step characterization – crystallization and staining (applied with a thin brush) were performed in a single step with one firing cycle (850 °C/10 min); and DC – double-step characterization – crystallization firing cycle was performed first (850 °C/10 min), followed by staining firing cycle (770 °C/90 s). Specimens were fired two, four or six times (one crystallization firing cycle and one, three or five staining firing cycles), resulting into 9 groups (n = 30): COII, COIV, COVI, SCII, SCIV, SCVI, DCII, DCIV and DCVI. The composition of the specimens was investigated (EDS, XRD, Raman spectroscopy), and the biaxial flexural strength (n = 10) and staircase tests (n = 20, 5 × 104 cycles, 5 Hz) were performed. Data were subjected to one-way ANOVA and Tukey's test (α = 0.05). Results: EDS and XRD revealed amorphous content for stained groups. Biaxial flexural strength was not affected by repeated firings in any group, but stained groups presented lower flexural strength than control groups (p = 0.001). The fatigue limit results decreased in all groups compared to flexural strength. SC groups showed similar (SCII and SCIV) or even higher fatigue limits (SCVI) than the control groups, and DC showed the lowest fatigue limit values. SEM and Raman suggested that the interfaces between staining and the LD showed only an overlap for the DC groups, whereas for the SC it was suggested an interaction between the stain and the LD. Significance: Repeated firings did not result in decreased lithium disilicate flexural strength.Staining affected flexural strength and also resulted in increased amorphous content in the characterized specimens. Single-step staining resulted in the highest fatigue limit.
Keywords: Glass ceramic; Lithium disilicate; Mechanical behavior; Staircase method